The Urgency of Religion in Preparing Mental Health According to Zakiah Daradjat - Jarman Arroisi; Dzatu Aliviatin Nuha; Rita Ashfuriyah; Khotimatul Mahbubah (Tasfiyah: Jurnal Pemikiran Islam, 2022)
As the term for the present age, the Millennial age is very full of various diseases that attack the biological side of humans and are rife in the community, including psychic and mental illnesses. That problem is usually characterized by uncontrolled morals as well as an uneasy soul. In this case, mental health becomes the main goal in healing the disease and makes many psychologists examine specifically mental health. In this regard, Zakiah Daradjat, the first Muslim psychologist in Indonesia, offers the best medicine for healing by presenting religion as a guide to human life. Using descriptive-analytical methods, the most important point found in this paper is that religion in daily life is very related and influential in fostering mental health because it has implications for controlling morals and calming one's soul.